Foundations of intelligent systems 19th International Symposium, ISMIS 2011, Warsaw, Poland, June 28-30, 2011. Proceedings - Kryszkiewicz, Marzena; Rybinski, Henryk; Skowron, Andrzej; Raś, Zbigniew W. (LNCS sublibrary. SL 7, Artificial intelligence, 2011)
This book constitutes the refereed proceedings of the 19th International Symposium on Methodologies for Intelligent Systems, ISMIS 2011, held in Warsaw, Poland, in June 2011. The 71 revised papers presented together with 3 invited papers were carefully reviewed and selected from 131 submissions. The papers are organized in topical sections on rough sets - in memoriam Zdzis?aw Pawlik, challenges in knowledge discovery and data mining - in memoriam Jan ?ytkov, social networks, multi-agent systems, theoretical backgrounds of AI, machine learning, data mining, mining in databases and warehouses, text mining, theoretical issues and applications of intelligent web, application of intelligent systems in sound processing, intelligent applications in biology and medicine, fuzzy sets theory and applications, intelligent systems, tools and applications, and contest on music information retrieval.